Static Mechanics and Dynamic Analysis and Control of Bridge Structures Under Multi-Load Coupling Effects - Zhifang, Ma; Zhuoyu, Sun; Yuan, Yuan (European Journal of Computational Mechanics, 2023)
With the rapid development and wide application of large-span bridges, the problem of dynamics and safety control of bridge structures under multiple loads is becoming more and more prominent. To realize the dynamic analysis and mechanical control of the girder structure, this paper designs a new type of magnetorheological (MR) mechanical damper based on the mechanistic analytical method and establishes a coupled dynamics model of the vehicle-rail-MR mechanical damper. The simulation and validation results show that the error between the semi-analytical method and the finite element theory calculation results is only 1.0%, while the kinetic simulation is consistent with the measured frequency domain trend. The analytical results show that: After applying MR mechanical damper for mechanical control, the moment live load and shear values of side spans were reduced by 27.68% and 10.79%, respectively; and the maximum moment and shear values generated at the center pivot were reduced by 28.19% and 10.81%, respectively. After applying the mechanical damper, the stress distribution of the cable-stayed bridge is more balanced, and the maximum diagonal stress of the overall structure is reduced from 3.8 MPa to 2.9 MPa. After safety control, the root-mean-square (RMS) value of the mid-span displacement amplitude was reduced by 59.32% and the maximum value was reduced by 11.46%, which improved the stability of the girder dynamics. After mechanical control, the dynamic acceleration response of the beam within the span decreased between 2 and 8 seconds and increased between 8 and 10 seconds. The overall response fluctuated around −5 m/s2 with a relatively smooth trend.